The nonprofit sector in Germany: between state, economy and society - Anheier, Helmut K.; Seibel, Wolfgang (Johns Hopkins nonprofit sector series, 2001)
This book offers an overview of the size, scope, structure, historical development and current policy environment of the German nonprofit sector.
Keywords: Bibliographie enthalten; Gemeinnütziges Unternehmen; Deutschland; Nonprofit-Bereich